Exploring the experiences of an autistic male convicted of stalking - Rawdon, Nikki (The journal of forensic psychiatry & psychology, 2024)
Despite an increasing number of studies which examine the interplay between autism and offending mechanisms, there has been a lack of research investigating the interplay between autism and stalking. It was anticipated that findings from this investigation would inform future interventions with individuals with autism who stalk. This secondary data analysis research used a qualitative case study approach to explore the experiences of an individual with a High Functioning Autism (HFA) diagnosis, who had been convicted of stalking. Interview data was analysed using Interpretative Phenomenological Analysis to gain a rich understanding of stalking behaviour from the perspective of the individual and to identify the key issues associated with Criminal Justice Service interventions. The following superordinate themes were identified; ‘What she means to me’, ‘Problematic, but unstoppable'’ and ‘Life after prison’. A key implication of the findings was that autistic traits can play a contextual role within stalking behaviour. Future recommendations of a specifically tailored treatment approach recognising and considering autism-related responsivity issues are discussed.